Grim-19 deficiency promotes decidual macrophage autophagy in recurrent spontaneous abortion - Yang, Yang; Liu, Haoran; Zhao, Yue; Geng, Chen; Chao, Lan; Hao, Aijun (Frontiers in Endocrinology, 2022)
Dysregulation of decidual macrophages leads to the occurrence of recurrent spontaneous abortion (RSA). However, the role of macrophages in RSA occurrence remains unclear. In this study, we found that the expression of Grim-19 was decreased, and the expression of autophagy related proteins Beclin1, LC3B II/I and BNIP3 was markedly upregulated in decidual macrophages of RSA patients compared with the normal pregnancy group. Furthermore, we demonstrated that downregulation of GRIM-19 increased the expression of autophagy related proteins Beclin1, LC3B II/I, BNIP3 and the proinflammatory cytokines IL1B, IL6 and TNFa in uterine mononuclear cells of GRIM-19+/- mice. The proportion of CD45+CD11b+F4/80+LC3B+ cells in GRIM-19+/- mouse uteri was significantly higher than that in WT mouse uteri. In addition, we confirmed that inhibition of Grim-19 by siRNA enhanced the expression of autophagy related proteins in RAW264.7 cells and THP-1 cells. More importantly, downregulation of Grim-19 in RAW264.7 cells promoted the release of proinflammatory cytokines and promoted phagocytic activity, which could be reversed by autophagy blockade. For THP-1-derived macrophages, the results of RNA-seq suggested that Grim-19 mainly modulates immune and inflammatory-related pathways, leading to cytokine production, and thus contributing to inflammation. Therefore, our data reveal that Grim-19 deficiency influences macrophage function, characterized by enhanced proinflammatory cytokines and phagocytic activity, and this might be regulated by autophagy. This may represent a novel mechanism for the occurrence of RSA.